Ultralight Electrolyte for High‐Energy Lithium–Sulfur Pouch Cells. (23rd June 2021) - Liu, Tao; Li, Huajun; Yue, Jinming; Feng, Jingnan; Mao, Minglei; Zhu, Xiangzhen; Hu, Yong‐sheng; Li, Hong; Huang, Xuejie; Chen, Liquan; Suo, Liumin
Abstract: The high weight fraction of the electrolyte in lithium–sulfur (Li–S) full cell is the primary reason its specific energy is much below expectations. Thus far, it is still a challenge to reduce the electrolyte volume of Li–S batteries owing to their high cathode porosity and electrolyte depletion from the Li metal anode. Herein, we propose an ultralight electrolyte (0.83 g mL −1 ) by introducing a weakly‐coordinating and Li‐compatible monoether, which greatly reduces the weight fraction of electrolyte within the whole cell and also enables Li–S pouch cell functionality under lean‐electrolyte conditions. Compared to Li–S batteries using conventional counterparts (≈1.2 g mL −1 ), the Li–S pouch cells equipped with our ultralight electrolyte could achieve an ultralow electrolyte weight/capacity ratio (E/C) of 2.2 g Ah −1 and realize a 19.2 % improvement in specific energy (from 329.9 to 393.4 Wh kg −1 ) under E/S=3.0 μL mg −1 . Moreover, more than 20 % improvement in specific energy could be achieved using our ultralight electrolyte at various E/S ratios. Abstract : Ultralight electrolytes with a density of 0.83 g mL −1 were proposed by introducing a weakly‐coordinating and Li‐compatible monoether. A weight reduction of more than 30 % per volume was realized relative to the conventional electrolyte, also enabling Li–S pouch cell functionality under lean‐electrolyte conditions. When applied in pouch cells, ≈20 % improvement in specific energy could be achieved at various E/S ratios.